Plankton Diversity in a River Nearby Klotok Landfill, Kediri, East Java - Restu Hikmah Ayu Murti; Thineza Ardea Pramesti; Isna Nugraha; Praditya Sigit Ardisty Sitogasa; Kabul Fadilah; Aussie Amalia; Muhammad Abdus Salam Jawwad (Future Science, 2022)
Landfill management in Indonesia is mostly operated by open dumping as well as the Klotok’s Landfill at Klotok Village, Kediri City. This landfill has three lands, and the third landfill is currently actively operating. The pollution is like the occurrence of leaks in leachate storage tanks which is near the Klotok river. That situation can make the leachate enter the river and affect the physicochemical conditions of the water which have an impact on decreasing the diversity and abundance of plankton. The diversity of plankton species in aquatic ecosystems is often used as an indicator to determine the primary productivity of waters and the condition of the aquatic ecosystem, so this research was carried out to determine the diversity of plankton species in the Klotok river, so the quality of the water can be known. This research was conducted in the Klotok River, Kediri City, East Java. Samples were taken upstream of the Klotok River, near the leachate treatment Plant, and downstream of the Klotok River. Samples were taken as much as 21 liters by pouring method. The samples are poured into plankton nets. The result shows that plankton diversity in the water body near Klotok landfill is between 0,49 to 0,67, which indicates that the diversity index according to Shannon-Wiener is 0,49 where the species diversity is low, the number of individual species is low, the ecosystem is unstable, and the waters are degraded.